Hydrometallurgy : fundamentals and applications - Free, Michael (Hoboken, New Jersey : TMS-Wiley, 2013)
'This book provides a college-level overview of chemical processing of metals in water-based solutions, in the field that is known as hydrometallurgy'--
Includes bibliographical references and index.
Keywords: Hydrometallurgy